Pendekatan Ekonomi Spasial Untuk Kejahatan Hak Milik Di Wilayah Polda Jawa Barat - Gelora Islami Putri (Center for Economic Studies Universitas Katolik Parahyangan, 2019)
Property crime is a crime with economic motives. Research on crime from an economic perspective is needed in Indonesia because of the limited study of crime behavior associated with socio-economic conditions, even though the number of crimes related to the region can be related to social, economic, and spatial factors. Socio-economic factors such as income and unemployment can be used to explain differences in crime amounts. Crime is analyzed with spatial aspects because crime events in one region can be associated with crime events in other areas that intersect. The purpose of this study is to verify the spatial dependence in cases of property crime in the West Java Regional Police. The West Java Regional Police are among the three regional police with the highest property crime in Indonesia. Socio-economic factors such as income and unemployment have a positive correlation with the number of property crime in the West Java Regional Police. Through spatial analysis using the global Moran index, the results of this study found that the number of property crime cases in Jawa Barat Regional Police did not have spatial autocorrelation. Through LISA, the results of research in the period 2013-2015, indicate a significant increase in the area each year. In 20 regencies/cities in Jawa Barat Regional Police, only five regencies have significant spatial correlations with their neighbors, namely Majalengka Regency, Tasikmalaya Regency, Kuningan Regency, Sukabumi Regency, and Purwakarta Regency. Keywords: property crime; socio-economic factors; spatial analysis; Jawa Barat Regional Police